Hubungan Motivasi Ibu dengan Deteksi Dini Kanker Serviks Melalui Metode Inspeksi Visual Asam Asetat (IVA) - Weni Lidya Hendayani; Hendrawati Hendrawati (Jurnal Pembangunan Nagari, 2019)
Cervix cancer has become women’s health problem that should get serious concern. One of the causes of death from cervical cancer is delayed detection. Data WHO in 2010, 500.000 new cases with death 280.000 suffered was happened every year in the world. These supposed to be minimized by primary prevention that is Pap Smear or IVA Test. The purpose of study was to determine mother motivation with of early cervix cancer detection through inspection of visual acid acetate (IVA). This study used cross sectional method. The study was conducted at Work Area Of Kebun Sikolos Comunity Healthy Center in March 2018. The research Sampling is eproductive age of women as many 138 people with purposif sampling technique. Data collection were managed by using questionnaire. Data analysis used chi-square statistic test. The result test show a influence between mother motivation with of early cervix cancer detection through inspection of visual acid acetate (IVA) with p-value 0,043 (α≤0,05). Ecpected to Comunity Healty Center to Improved knowledge of correct IVA examination procedures through the promotion of programmed and repeated health.